2021
DOI: 10.3389/fmed.2021.620050
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Due to COVID-19 in Intensive Care Unit: An Analysis From a Latin-American Center

Abstract: Introduction: The kidney may be affected by coronavirus (COVID-19) in the setting of acute kidney injury (AKI). Data about AKI in intensive care unit (ICU) patients in Latin America are scarce. We aimed to evaluate the risk of AKI, dialysis (HD), and death in ICU COVID-19 patients in a Brazilian center.Methods: Analysis from medical records of COVID-19 patients in a Brazilian center.Results: A total of 95 patients were analyzed. There was male predominance (64.2%), median age: 64.9 years, and previous history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
0
9
0
9
Order By: Relevance
“…Gutiérrez-Abejón et al reported a doubling of the mortality rate in patients with COVID-19 and AKI [ 34 ]. Other studies have also demonstrated that AKI is associated with an increased risk of death [ 35 , 36 ]. Patients with a high creatinine level and a low GFR at admission to the ICU had worse outcomes in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Gutiérrez-Abejón et al reported a doubling of the mortality rate in patients with COVID-19 and AKI [ 34 ]. Other studies have also demonstrated that AKI is associated with an increased risk of death [ 35 , 36 ]. Patients with a high creatinine level and a low GFR at admission to the ICU had worse outcomes in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The studies originated from multiple countries, with 13 of coming from institutions located in the USA [20,21,23,[32][33][34][35]38,42,43,45,48,51]. Nineteen studies included only patients admitted in the ICU [20,22,24,25,27,[30][31][32][35][36][37][38][39][43][44][45][46][47]52], five studies included patients admitted in a COVID-19-dedicated HDU [28,29,33,34,42], eight studies included patients who were admitted in both HDU and ICU [21,23,26,40,41,48,49,51], and one study included Emergency Department patients who were later admitted either in the HDU of ICU [50]. Thirty studies included data about patients who received vs. patients who did not receive vasopressors…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Twenty-one out of the 33 included studies provided data on hospital mortality in patients who received vs. patients who did not receive vasopressors, resulting in a total population of 7900 individuals [25,27,[31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][48]50,52]. Due to high heterogeneity (I 2 : 94%, PQ<0.001), the random-effects model was implemented.…”
Section: Primary Outcomementioning
confidence: 99%
“…All the 34 included studies were observational in their design [ 21 54 ]. Twenty studies included only patients admitted to the ICU [ 21 , 23 , 25 , 26 , 28 , 31 – 33 , 36 40 , 44 48 , 53 , 54 ], five studies included patients admitted to a COVID-19-dedicated HDU [ 29 , 30 , 34 , 35 , 43 ], eight studies included patients who were admitted to both HDU and ICU [ 22 , 24 , 27 , 41 , 42 , 49 , 50 , 52 ], and one study included Emergency Department patients who were later admitted either to ICU [ 51 ]. Thirty-one studies included data about patients who received vs. patients who did not receive vasopressors [ 21 38 , 40 49 , 51 , 53 , 54 ] and were included in review.…”
Section: Resultsmentioning
confidence: 99%